Safety and Quality of Nutraceuticals: Have FSSAI Guidelines been Able to Blaze the Trail? - Dande, Payal; Samant, Purva; Singh, Yashita; Sheth, Umang (Applied Clinical Research, Clinical Trials and Regulatory Affairs, 2020)
The nutraceutical industry has three main segments, including herbal/- natural products, dietary supplements and functional foods. The dietary supplements market is preliminarily driven by the paradigm shift towards preventive health management practices, amid rising healthcare costs and increasing burden of lifestyle diseases. Rise in healthcare expenditure, increased usage of nutraceuticals product as a substitute to prescription and OTC drugs and augmented demand for the nutritional diet are the major factors driving the global nutraceuticals market. Many individual laws were devised to govern its manufacturing and sale. However, increasing regulatory formalities from multiple agencies and laws, complicate the development, testing and marketing of these substances and hamper the growth of the nutraceutical market. Globally, the regulatory authorities are aware of the changing needs of consumers and proactively protect consumers by amending existing laws to accommodate changes. Market entry requirements of nutraceuticals, functional foods and supplements vary from country to country. The global regulatory guidelines aim at regulating various aspects of the nutraceutical and dietary supplements market, focusing on its manufacture, testing, labeling, sale and registration to assure safety and quality of the product. The major change that was introduced was the ban on marketing Nutraceuticals as medicinal products. This review has been performed to provide a comprehensive understanding of the global regulatory requirements with critical analysis of the Indian regulatory guidelines to explore the lacunae and suggest the need of further amendments in the form of recommendations that can be incorporated into regulatory body guidelines to make it more competitive for national & international trade.
Keywords: prebiotics